Innate immunity and malaria - Golenbock, Douglas (Henry Stewart Talks, 2009)
Malaria causes systemic inflammation, morbidity and death, Toxic mediators: GPI anchor, Hemozoin/DNA, DNA motifs: CpG (TLR9) and AT-rich (unknown receptor), Mechanisms of malarial sepsis-like syndrome, cerebral malaria